Finite-dimensional approximations of diffusion measures in a Hilbert space - Bondarenko, V. G. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
For transition probabilities of diffusion processes in a Hilbert space, we construct finite-dimensional approximations and establish sufficient conditions for the equivalence of such measures under perturbation of the diffusion operator.